APRESENTAÇÃO - Benite, Anna M. Canavarro; Vianna, Cintia Camargo; Figueiredo, Mércia Otaviana Barbosa de Sá; Baruty, José Antonio Novaes da Silva (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2019)
**